Cardiomyocyte binucleation is associated with aberrant mitotic microtubule distribution, mislocalization of RhoA and IQGAP3, as well as defective actomyosin ring anchorage and cleavage furrow ingression. Issue 8 (7th March 2018) - Leone, Marina; Musa, Gentian; Engel, Felix Benedikt
Abstract: Aims: After birth mammalian cardiomyocytes initiate a last cell cycle which results in binucleation due to cytokinesis failure. Despite its importance for cardiac regenerative therapies, this process is poorly understood. Here, we aimed at a better understanding of the difference between cardiomyocyte proliferation and binucleation and providing a new tool to distinguish these two processes. Methods and results: Monitoring of cell division by time-lapse imaging revealed that rat cardiomyocyte binucleation stems from a failure to properly ingress the cleavage furrow. Astral microtubule required for actomyosin ring anchorage and thus furrow ingression were not symmetrically distributed at the periphery of the equatorial region during anaphase in binucleating cardiomyocytes. Consequently, RhoA, the master regulator of actomyosin ring formation and constriction, non-muscle myosin IIB, a central component of the actomyosin ring, as well as IQGAP3 were abnormally localized during cytokinesis. In agreement with improper furrow ingression, binucleation in vitro and in vivo was associated with a failure of RhoA and IQGAP3 to localize to the stembody of the midbody. Conclusion: Taken together, these results indicate that naturally occurring cytokinesis failure in primary cardiomyocytes is due to an aberrant mitotic microtubule apparatus resulting in inefficient anchorage of the actomyosin ring to the plasma cell membrane. Thus, cardiomyocyte binucleation and division can be discriminated by the analysis of RhoA as well as IQGAP3 localization.